Requirement Model For Class Management System (CMS) - Nurul Izzah, Maharudin (2007)
The increasing numbers of students in both primary and secondary schools in Malaysia demand a more efficient and systematic system to handle interactions between the School Administration, Teachers and Parents. Besides, the teacher's responsibilities and tasks are increasing especially for those who are being class teacher because he has to manage their student's records and control a big number of students in the class. Class Management System (CMS) is proposed to be a web-based system that enables better communication regardless of time, and location of the users. In order to develop an effective support for CMS, the developers or system analysts need to thoroughly understand the requirements to build the system. Thus, this study which is to design requirement model for CMS have most contributed to solve the problem. The Unified Modeling Language (UML) specifically the User Experience (UX) Model has been utilized to design Requirement Model for CMS aims to provide a standard understanding of the overall requirements for CMS. The study uses the Unified Software Development Process (USDP) which consists of inception, elaboration, construction and transition phase. However, in this study only functional requirements be captured. Requirement model is validated by using system requirement testing, horizontal prototype and test case. UML diagrams and a set of requirements list will be produced in this study. This study was concluded by summarizing overall result and discussing the findings as well as constraints and limitations arising during the course of producing the model. The recommendation for future study also is propose.